Stabilitas Ukuran Nanoemulsi Parfum Campuran Minyak Atsiri Black Musk dan Lili yang Dienkapsulasi dengan Polimer Tween 80 - Ginting, Endru Saperlin Lawren; Saragih, Horasdia (Jurnal Fisika Unand, 2026)
In this study, a perfume mixture of black musk and lily essential oils was nanoemulsified using a tween 80 polymer encapsulator and dispersed in water to produce a water-based perfume. Water was used as a base to replace alcohol, which often causes side effects on the skin. Its size stability was tested, both as a result of storage time and as a result of heating. The purpose of this study was to produce a water-based perfume from a nanoemulsion mixture of black musk and lily essential oils, and to test its size stability. Nanoemulsion was carried out using an atomization technique. The results showed that the average diameter and standard deviation of the nanoemulsion changed after being stored for 120 days and when heated to a temperature of 45oC. The size change during storage was mainly caused by the very small zeta potential, which did not produce sufficient electrostatic repulsion between the nanoemulsions to prevent Ostwald ripening and coalition. The size change due to heating, in addition to the above, was also caused by the increasing kinetic energy of the tween 80 polymer molecules on the surface of the nanoemulsion, which caused a reorganization (solidification) of its structure. Thus, the stability of the size of the nanoemulsion perfume mixture of black musk and lily essential oils produced in this study was greatly influenced by storage time and heating temperature.